End-of-day dryness, corneal sensitivity and blink rate in contact lens wearers - Martín-Montañez, Vicente (2015)
Purpose: To study the relationship among the variables intensity ofthe end-of-day (EOD) dryness, corneal sensitivity and blink rate in soft contact lens (CL) wearers. Methods: Thirty-eight soft CL wearers (25 women and 13 men; mean age 27.1 ± 7.2 years) were enrolled. EOD dryness was assessed using a scale of 0–5 (0, none to 5, very intense). Mechanical and thermal (heat and cold) sensitivity were measured using a Belmonte’s gas esthesiometer. The blink rate was recorded using a video camera while subjects were wearing a hydrogel CL and watching a film for 90 min in a controlled environmental chamber. Results: A significant inverse correlation was found between EOD dryness and mechanical sensitivity (r: −0.39; p = 0.02); however, there were no significant correlations between EOD dryness and thermal sensitivity. A significant (r: 0.56; p < 0.001) correlation also was observed between EOD dryness and blink rate, but no correlations were found between blink rate and mechanical or thermal sensitivity. Conclusions: CL wearers with higher corneal sensitivity to mechanical stimulation reported more EOD dryness with habitual CL wear. Moreover, subjects reporting more EOD dryness had an increased blink rates during wear of a standard CL type. The increased blink rate could act to improve the ocular surface environment and relieve symptoms